Boron nitride materials: an overview from 0D to 3D (nano)structures. (30th April 2015) - Arenal, Raul; Lopez‐Bezanilla, Alejandro
Abstract : Boron nitride (BN) materials present different crystalline phases including fullerene‐like (0D), nanotubes (1D, NTs), hexagonal (2D, h‐BN), and cubic (3D) structures. These materials show a rich variety of physical and chemical properties with multiple potential applications in industry, science, and technology, especially in the fields of nano‐electronics, optoelectronics, field emission, and lubrication in extreme conditions of temperature. BN compounds are chemically and thermally very stable and resistant to oxidation. The large electronic band gap confers to BN compounds complementary electronic properties to the C allotropes with similar structure. The combination of BN and C materials forming heterostructures has gained an increasing importance in the nano‐sciences. In particular, heterostructures combining graphene with mono‐ and multi‐layer h‐BN, or C‐ with BN‐nanotubes are the object of intensive study in nano‐sciences due to their unique electronic properties. Applications based on BN structures have created great expectations and offer enormous possibilities in the next generation of electronic devices. However, the massive production of high‐quality defect‐free BN materials is still an experimental challenge. WIREs Comput Mol Sci 2015, 5:299–309. doi: 10.1002/wcms.1219 This article is categorized under: Structure and Mechanism > Computational Materials Science Electronic Structure Theory > Ab Initio Electronic Structure Methods Theoretical and Physical Chemistry > Spectroscopy Abstract :